Development of a cryocatcher prototype and measurement of cold desorption. (4th May 2016) - Bozyk, L.; Hoffmann, D.H.H.; Kollmus, H.; Spiller, P.
Abstract: The superconducting synchrotron SIS100 of the FAIR accelerator project will provide heavy ion beams of highest intensities. SIS100 is the first synchrotron with a special design, optimized for the control of ionization beam loss. Ionization beam loss is the most pronounced loss mechanism at operation with high-intensity, intermediate charge state heavy ions. The new synchrotron layout comprises an ion catcher system, which in combination with a charge separator lattice shall suppress dynamic vacuum effects. A prototype cryogenic ion catcher, including a dedicated cryostat has been designed, manufactured, and tested under realistic conditions with beams from the heavy-ion synchrotron SIS18 at GSI. The gas desorption induced by the impact of heavy ions on this cryocatcher has been measured. For the very first time, a rise of desorption yield with increasing beam energy has been observed. However, measurements at room temperature have confirmed the known decrease of the pressure rise in the investigated energy regime. A transition temperature of 18 K, underneath hydrogen is adsorbed, could be verified several times. The results are significant and used to predict the ionization beam loss at operation of SIS100 at full-beam intensity.